Differential CD4+ T-Cell Cytokine and Cytotoxic Responses Between Reactivation and Latent Phases of Herpes Zoster Infection - Wenjie Jin; Mike Fang; Ismail Sayin; Carson Smith; Jeffrey Hunter; Brian Richardson; Jackelyn Golden; Christopher Haley; Kenneth Schmader; Michael Betts; Cheryl Cameron; Stephen Tyring; et al. (Case Western Reserve University, 2023)
Background: CD4+ T cells are a critical component of effective immune responses to varicella zoster virus (VZV), but their functional properties during the reactivation acute vs latent phase of infection remain poorly defined. Methods: Here we assessed the functional and transcriptomic properties of peripheral blood CD4+ T cells in persons with acute herpes zoster (HZ) compared to those with a prior history of HZ infection using multicolor flow cytometry and RNA sequencing.  Results: We found significant differences between the polyfunctionality of VZV-specific total memory, effector memory, and central memory CD4+ T cells in acute vs prior HZ. VZV-specific CD4+ memory T-cell responses in acute HZ reactivation had higher frequencies of IFN-γ and IL-2 producing cells compared to those with prior HZ. In addition, cytotoxic markers were higher in VZV-specific CD4+ T cells than non-VZV-specific cells. Transcriptomic analysis of ex vivo total memory CD4+ T cells from these individuals showed differential regulation of T-cell survival and differentiation pathways, including TCR, cytotoxic T lymphocytes (CTL), T helper, inflammation, and MTOR signaling pathways. These gene signatures correlated with the frequency of IFN-γ and IL-2 producing cells responding to VZV.  Conclusions: In summary, VZV-specific CD4+ T cells from acute HZ individuals had unique functional and transcriptomic features, and VZV-specific CD4+ T cells as a group had a higher expression of cytotoxic molecules including Perforin, Granzyme-B, and CD107a.